REDUCED LENGTH OF STAY IN CHILDREN WITH DIARRHEA FOLLOWING IMPLEMENTATION OF CLINICAL PATHWAY - Suwedia, I Nyoman Gede Bayu Wiratama; Nurwahyuni, Atik (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Diarrhea or Acute Gastroenteritis (AGE) is a dissease that common found in toddlers at emergecy room. The complication of diarrhea such as dehydration may go undetected by parents will affect the treatment and length of stay in the hospital. Decreasing the length of stay in the hospital can be done by implementing clinical pathways. This study aims to examine the effect of implementing clinical pathways on length of stay in children with diarrhea. Methods: This study was a systematic review that used PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines. Data obtained from Electronic databases Proquest and Scopus that published between 2009-2019 and used English. By using keywords such as clinical pathway, gastroenteritis, and length of stay to find the relevant articles. Results: The search found 610 studies, of which 6 studies were included in the systematic review. These studies conducted majority in USA and 1 study in Australia. Analysis of the studies found out that implemented clinical pathway can decrease length of stay 0.4 days (95% CI 0.04 to 0.7, p <0.01). The decreased of length of stay can increased 2.5% (CI 0.25% to 4.38%) used of medical beds then the bed can be more effective and used by other patients. Conclusion: Implementing clinical pathway in the treatment process of diarrhea towards children not only reduce the length of stay in hospital but also useful in providing patient diagnosed and reduce the bed use per day and year.